FAKTOR YANG MENENTUKAN MUZAKKI BERDONASI KEMBALI DI LEMBAGA ZAKAT - Basit, Abdul; jaenudin, muhammad; Ratnasari, Ririn Tri (Universitas Muhammadiyah Surabaya, 2022)
This study aims to determine the muzakki's factors to re-donate in LAZNAS IZI. In addition, this study also wants to know the effect of service quality factors and the institution's reputation on the intention to re-donate at LAZNAS IZI. This study uses multiple linear regression by testing the effect of the Independent variables (X) on the Dependent variable (Y). There are four independent variables, namely Service Quality (X1), Reputation (X2), Attitude (X3), and Trust (X4). The dependent variable used is Intention to Redonation (Y). Primary data were obtained from questionnaires distributed to 97 IZI Zakat Institution donors who had donated more than once. From this research, it can be seen that Service Quality partially influences the interest to donate Back to IZI Zakat Institution. While Reputation, Attitude, and Trust partially have no effect. However, simultaneously all variables affect the interest of donors to re-donate to LAZNAS IZI. This study can be used by LAZNAS IZI as a reference to maintain several variables that are factors that donors are willing to redonation. In addition, variables that do not have a direct effect need to be developed with other variables together to have an effect and increase the donor's intention to redonation. The addition of the number of respondents and LAZ studied can also enrich the results of subsequent studies